Comparative Propensity Matched Outcomes in Severe COVID-19 Respiratory Failure—Extracorporeal Membrane Oxygenation or Maximum Ventilation Alone. Issue 5 (November 2021) - Mustafa, Asif K.; Joshi, Devang J.; Alexander, Philip J.; Tabachnick, Deborah R.; Cross, Chadrick A.; Jweied, Eias E.; Mody, Nitesh S.; Huh, Marc H.; Fasih, Subia; Pappas, Pat S.; Tatooles, Antone J.
Abstract : Objective: Does extracorporeal membrane oxygenation (ECMO) improve outcomes in ECMO-eligible patients with COVID-19 respiratory failure compared to maximum ventilation alone (MVA)? Summary Background Data: ECMO is beneficial in severe cases of respiratory failure when mechanical ventilation is inadequate. Outcomes for ECMO-eligible COVID-19 patients on MVA have not been reported. Consequently, a direct comparison between COVID-19 patients on ECMO and those on MVA has not been established. Methods: A total of 3406 COVID-19 patients treated at two major medical centers in Chicago were studied. One hundred ninety-five required maximum ventilatory support, and met ECMO eligibility criteria. Eighty ECMO patients were propensity matched to an equal number of MVA patients using detailed demographic, physiological, and comorbidity data. Primary outcome was survival and disposition at discharge. Results: Seventy-one percent of patients were decannulated from ECMO. Mechanical ventilation was discontinued in 75% ECMO and 16% MVA patients. Twenty-five percent of patients in the ECMO arm expired, 21% while on ECMO, compared with 74% in the MVA cohort. Mortality was significantly lower across all age and BMI groups in the ECMO arm. Sixty-eight percent ECMO and 26% MVA patients were discharged from the hospital. Fewer ECMO patients required long-term rehabilitation. Major complications such as septic shock, ventilator associated pneumonia, inotropic requirements, acute liver and kidney injuries are less frequent among ECMO patients. Conclusions: ECMO-eligible patients with severe COVID-19 respiratory failure demonstrate a 3-fold improvement in survival with ECMO. They are also in a better physical state at discharge and have lower overall complication rates. As such, strong consideration should be given for ECMO when mechanical ventilatory support alone becomes insufficient in treating COVID-19 respiratory failure. Abstract : Supplemental Digital Content is available in the text